2017
DOI: 10.1007/s13577-017-0175-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of HepaRG cells for the assessment of indirect drug-induced hepatotoxicity using INH as a model substance

Abstract: HepaRG cells are widely used as an in vitro model to assess drug-induced hepatotoxicity. However, only few studies exist so far regarding their suitability to detect the effects of drugs requiring a preceding activation via the cytochrome P450 (CYP) system. A prototypic substance is the anti-tuberculosis agent INH, which is metabolized into N-acetylhydrazine, which then triggers hepatotoxicity. Therefore, the aim of the present study was to test if this effect can also be detected in HepaRG cells and if it can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 66 publications
5
12
0
Order By: Relevance
“…the most efficacious within a specific window of INH concentrations that are neither too severe nor too mild. This observation is consistent with other in vitro findings, which involve the characterisation of silibinin's hepatoprotective effects at toxicant concentrations around the IC 50 values of their respective assays (Mann et al, 2017;Singh et al, 2012). The existence of INH's "Goldilocks zone" has two clinical implications in discussing silibinin's role as a rescue adjuvant.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…the most efficacious within a specific window of INH concentrations that are neither too severe nor too mild. This observation is consistent with other in vitro findings, which involve the characterisation of silibinin's hepatoprotective effects at toxicant concentrations around the IC 50 values of their respective assays (Mann et al, 2017;Singh et al, 2012). The existence of INH's "Goldilocks zone" has two clinical implications in discussing silibinin's role as a rescue adjuvant.…”
Section: Discussionsupporting
confidence: 90%
“…The optimal silibinin concentration from our viability experiments was determined to be 25 μ M when DILI was induced with 80 mM INH ( Fig. 2A), which may be explained by silibinin's pro-oxidative and pro-apoptotic effects at higher concentrations, an observation that corroborates experiments conducted by other research groups in rats (Malekinejad et al, 2012) and other in vitro cell lines (Mann et al, 2017;Procházková et al, 2011;Surai, 2015).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…21 Our 3D liver spheroid model was built using human HepaRG™, which is considered a good hepatic model, as it exhibits high and stable secretion of albumin and metabolic capacity. [22][23][24][25] Multiple studies have shown that the toxicity of the anti-tuberculosis agent isoniazid, 26 acetaminophen, 27 or aflatoxin B1 (AFB1) 28 could be predicted accurately using 3D liver spheroid models. For the lung/liver-on-a-chip system, the 3D organotypic bronchial culture was prepared using normal human bronchial epithelial (NHBE) cells cultured at the ALI.…”
Section: Introductionmentioning
confidence: 99%